Pengembangan Potensi Lokal dan Kesejahteraan Desa Air Putih melalui KKN Berbasis Masjid - Evi Selva Nirwana; Syafrullah Febrima; Lola Inta Permata; Nurjana Heli Yensi; Ilman Zikrah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study focuses on the potential development and welfare improvement in Air Putih Village, Talang Empat, Bengkulu Tengah, where local resources have yet to be fully optimized. The primary issues include the lack of youth empowerment programs, limited community participation in religious and social activities, and insufficient economic initiatives utilizing local resources. The objective of this research is to address these challenges through a mosque-based community service program, integrating social, educational, and economic activities. The approach adopted is participatory, involving direct community engagement in planning and executing activities such as health education, economic empowerment through the production of Kalamansi syrup, and environmental sustainability efforts. The results demonstrate increased community participation in both religious and social activities, enhanced academic performance of students, improved youth health awareness, and a boost in local economic income. The success of this program underscores the importance of mosque-centered initiatives in fostering community development and social welfare.